Progression of osteoarthritis as a state of inertia. Issue 6 (30th June 2012) - Felson, David; Niu, Jingbo; Sack, Burton; Aliabadi, Piran; McCullough, Charles; Nevitt, Michael C
Abstract : Objectives: To test whether knees which recently developed disease were at higher risk for subsequent x-ray progression than knees which had been stable, suggesting that recent change produces further change and recent stability yields subsequent stability (a pattern of inertia). Methods: We used central readings of the annual posteroanterior x-rays obtained in the Osteoarthritis Initiative (OAI) focusing on change in Kellgren and Lawrence (KL) grade and change in semiquantitative joint space. We examined whether knees that had developed incident disease (KL grade 2) were at higher risk of subsequent progression than knees that were already grade 2 and had had stable disease. We combined data from multiple examinations. Using generalised estimating equations to adjust for the correlation between knees, we carried out logistic regression evaluating the risk for disease progression testing incident versus stable disease adjusting for age, sex, body mass index, physical activity, quadriceps strength and mechanical alignment. Results: 1562 OAI subjects with grade 2 disease had a mean age of 61.8 years, mean BMI of 29.4, and 61.7% were women. Of knees with stable disease, 4.1% showed progression within the next 12 months in KL grade versus 13.7% in those with incident disease (adjusted OR 4.0; 95% CI 2.4 to 6.7). For progression of joint space loss, we found a similar relation with incident versus stable disease (adjusted OR 5.3; 95% CI 3.6 to 7.9). Conclusions: Knee osteoarthritis radiographic progression follows a pattern of inertia. Factors that trigger the transition from stable disease to progression should be sought.